Development of schizogenous intercellular spaces in plants - Ishizaki, Kimitsune (Frontiers in Plant Science, 2015)
Gas exchange is essential for multicellular organisms. In contrast to the circulatory systems of animals, land plants have tissues with intercellular spaces (ICSs), called aerenchyma, that are critical for efficient gas exchange. Plants form ICSs by two different mechanisms: schizogeny, where localized cell separation creates spaces; and lysogeny, where cells die to create intercellular spaces. In schizogenous ICS formation, specific molecular mechanisms regulate the sites of cell separation and coordinate extensive reorganization of cell walls. Emerging evidence suggests the involvement of extracellular signaling, mediated by peptide ligands and leucine-rich repeat receptor-like kinases, in the regulation of cell wall remodeling during cell separation. Recent work on the liverwort Marchantia polymorpha has demonstrated a critical role for a plasma membrane-associated plant U-box E3 ubiquitin ligase in ICS formation. In this review, I discuss the mechanism of schizogenous ICS formation, focusing on the potential role of extracellular signaling in the regulation of cell separation.